MICRO- AND MESOPOROUS CARBON FORMS, CHRYSOTILE, AND CLATHRATES - Mellini M. (My University, 2005)
This chapter offers a not-exhaustive overview of structural mesoporosity in selected, natural mineral phases (carbon forms, chrysotile, gas hydrates). After a short introduction devoted to the introduction of the most general features of porosity, attention will be paid mostly to natural mesoporous mineral phases, leaving microporosity to other chapters of this volume. However, a few peculiar microporous structures will be also considered, because of their close resemblance with the mesoporous substances.
Keywords: structural mesoporosity; carbon forms; chrysotile; gas hydrates